2018
DOI: 10.1038/s41372-018-0258-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing decision making in neonatology: inhaled nitric oxide in preterm infants

Abstract: Objective: We studied decision-making regarding inhaled nitric oxide (iNO) in preterm infants with Pulmonary Hypertension (PH). Study Design: We asked members of the AAP-Society of Neonatal-Perinatal Medicine and Division-Chiefs to select from three management options-initiate iNO, engage parents in shared-decision-making or not consider iNO in an extremely preterm with PH followed by rating of factors influencing their decision. Results: 304… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The use of iNO in preterm infants with hypoxemic respiratory failure and pulmonary hypertension is controversial. [ 32 , 33 , 34 , 35 ] When used with high concentrations of oxygen, iNO can increase nitrosative stress. [ 9 ] Using iNO adds a significant risk of generating toxic nitrosative derivatives such as nitro-tyrosine, nitro-albumin and highly toxic perioynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…The use of iNO in preterm infants with hypoxemic respiratory failure and pulmonary hypertension is controversial. [ 32 , 33 , 34 , 35 ] When used with high concentrations of oxygen, iNO can increase nitrosative stress. [ 9 ] Using iNO adds a significant risk of generating toxic nitrosative derivatives such as nitro-tyrosine, nitro-albumin and highly toxic perioynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…According to Manja et al a national survey showed that most neonatologists continue to prescribe iNO to pre-term newborns based on the imperative that physicians should “do something/do everything” to treat HRF on maximal ventilatory support ( 119 ). Taken together, these data make clear that clinicians remain uncertain about the possible benefits of iNO in the vulnerable population of extremely pre-term infants, mainly due to a lack of studies on its efficacy in treating specific medical conditions in this population.…”
Section: Major Controversies Of Ino Use In Pre-term Newbornsmentioning
confidence: 99%
“…Physician Decision-Making at the Bedside Several studies 60,61 suggest that neonatologists do not consistently follow evidence-based clinical practice recommendations, which may be due to multiple factors. 26 A recent mixed-methods study of neonatologists to explore factors that influence bedside decision-making concerning the use of iNO in infants born extremely preterm in HRF was assessed by a vignette-based survey among neonatal members of the American Academy of Pediatrics (AAP). The AAP Perinatal Committee does not recommend the routine use of iNO in infants born extremely preterm but did not specify alternative recommendations for the management of PPHN in infants born preterm.…”
Section: Evidence From Observational Studies: Impact Of the Nih Statementioning
confidence: 99%
“…27 Among survey participants who responded to this case vignette of an infant born preterm with HRF, only 21% chose not to use iNO. 26 A clear majority chose to either initiate iNO therapy or engage parents in shared decision-making. Comments from participants suggested that factors other than knowledge of the evidence and of clinical practice guideline recommendations played a decisive role in clinical decision-making.…”
Section: Evidence From Observational Studies: Impact Of the Nih Statementioning
confidence: 99%
See 1 more Smart Citation